Plants' Contributions to People Shift With Glacier Extinction - Khelidj, N.; Balestra, S.; Caccianiga, M. S.; Cerabolini, B. E. L.; Tampucci, D.; Losapio, G. (Plant-environment interactions (Hoboken, N.J. : 2018), 2025)
ABSTRACT Alpine environments are among the most vulnerable ecosystems to climate change, with glacier retreat rapidly altering plant communities, biodiversity, and ecosystem functions. However, the socio‐economic consequences of these biodiversity changes remain largely unexplored. Understanding Nature's Contributions to People (NCP) provides a valuable framework for assessing biodiversity's role in human well‐being. While NCP has typically been studied at the landscape level, we focus on species‐specific contributions of plants to highlight the importance of glacial biodiversity for people. Our novel concept of Plants' Contributions to People (PCP) provides insights into the ecological, social, and economic significance of plant biodiversity and offers a practical approach for guiding conservation efforts and policy decisions. We surveyed 99 plant species in four glacier environments in the Italian Alps; one glacier (Trobio) underwent a complete extinction in 2023 while another glacier (Amola) has a widespread surface debris cover and is proximate to extinction. We then grouped plant species into early, intermediate, and late depending on their successional stages, and then linked plants to 13 different PCP based on extensive literature research. By comparing present and projected future scenarios, we assessed the absolute and relative changes in PCP under glacier extinction. Our results show that changes in PCP are primarily driven by declining plant species richness. Most affected PCP are associated with air quality, soil health, and nutrient regulation, which decrease by sevenfold on average across plant species. Whereas natural hazards regulation showed no significant variation, association with pest and disease increases especially for late species. While future plant communities may provide PCP that are qualitatively similar to present‐day communities, the volume of species‐specific contributions would decrease due to biodiversity loss associated with glacier extinction. Our results provide the first evidence of PCP shift toward erosion following a decrease in plant species richness. This case study demonstrates that PCP is a valuable tool for assessing the ecological and socio‐economic consequences of biodiversity change, helping raise awareness of the biodiversity crisis and inform conservation actions aimed at sustaining ecosystem functions in a rapidly changing world.